2013
DOI: 10.1177/1362361313500381
|View full text |Cite
|
Sign up to set email alerts
|

Verbal fluency in children with autism spectrum disorders: Clustering and switching strategies

Abstract: This study highlights differences in cognitive strategies in children and adolescents with and without autism spectrum disorders (n = 52) on a verbal fluency task (naming as many words as possible (e.g. animals) within 60 s). The ability to form clusters of words (e.g. farm animals like "cow-horse-goat") or to switch between unrelated words (e.g. "snake" and "cat") was analyzed using a coding method that more stringently differentiates between these strategies. Results indicated that children and adolescents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 26 publications
(42 reference statements)
6
56
2
6
Order By: Relevance
“…According to Begeer et al (2014), children with ASD produce errors in clustering and switching in a verbal fluency task, suggesting that these features may be linked to cognitive flexibility. Since shifts in executive function are one of the components comprising cognitive flexibility, it is possible that the language function (verbal fluency) is related to this shift.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Begeer et al (2014), children with ASD produce errors in clustering and switching in a verbal fluency task, suggesting that these features may be linked to cognitive flexibility. Since shifts in executive function are one of the components comprising cognitive flexibility, it is possible that the language function (verbal fluency) is related to this shift.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were obtained from only three cases; therefore, larger scale studies are needed to clarify the relationship between spontaneous speech and shifts in attentional flexibility. Previous studies have shown a correlation between vocabulary and similarity scores in intelligence tests (Begeer, Wierda, Scheeren, Teunisse, Koot, & Geurts, 2014). As we only examined the relationship between spontaneous speech and executive function, further research is required to investigate the relationship between other types of speech and execution function.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eredményeink felhívják a figyelmet arra, hogy a fluenciafeladatok idői elemzése olyan hasznos és fontos információkkal szolgál, amelyek segíthetik a neuropszichológiai és az iskolapszichológiai vizsgálatokat egyaránt. A jövőben érdemes lehet alkalmazni ehhez hasonló elemzéseket olyan atipikus fejlődést mutató csoportoknál, mint az autizmus, ADHD, diszlexia és más tanulási zavarok (Begeer et al, 2013;Takács et al, 2014). Ezek segítségével pontosabban feltérképezhetők az automatikus és a kontrollált folyamatok, valamint segítséget nyújthatnak az eltérő fejlődésű személyek fejlesztésének, tanítási-tanulási stratégiáinak átgondolásában, kialakításában.…”
Section: öSszegzés Eredmények éRtelmezéseunclassified